HONORARY LABOR RELATIONS IN THE GOVERNMENT SYSTEM IN INDONESIA - Hardrian Hardrian; Ani Wijayati; Andari Yurikosari (Jurnal Scientia, 2023)
Recruitment of non-staff employee is still done by the government institutions although the prohibition of recruit has been issued through Government Regulation Number 48 Year 2005. The existence of mortorium on acceptance non-staff employee. The status of non-staff employee becomes unclear when Law Number 5 of 2014 removes the existence of non-staff employee. This study aims to find out the employment relationship to non-staff employees and application of the PKWT (Temporary Work Agreement) provisions for non-staff employees. The research method used is juridical normative. The research results showed that the legal relationship that occurs to the non-staff employee has covered the elements of work: order, job, wages and time (condition) that must be met in a working relationship. The implementation of PKWT’s provision to non-staff employee can be applied by appointing non-staff employee as Candidate of Civil Servant in accordance with Government Regulation Number 48 Year 2005, while for non-staff employee recruited after 2005 will be applied as a regular contract subject to private law. The absence of regulation regarding non-staff employee causes a difficulty of providing protection for non-staff employee and potentially conflict in the future.